2021
DOI: 10.1186/s12929-021-00776-w
|View full text |Cite
|
Sign up to set email alerts
|

ROR2 has a protective role in melanoma by inhibiting Akt activity, cell-cycle progression, and proliferation

Abstract: Background Receptor tyrosine kinase-like orphan receptor 2 (ROR2) is a Wnt5a receptor aberrantly expressed in cancer that was shown to either suppress or promote carcinogenesis in different tumor types. Our goal was to study the role of ROR2 in melanoma. Methods Gain and loss-of-function strategies were applied to study the biological function of ROR2 in melanoma. Proliferation assays, flow cytometry, and western blotting were used to evaluate cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…ROR2 played as a tumor promoter in non‐small cervical cancer (Sun et al 2015), renal cell carcinoma (Wright et al 2009; Yang et al 2017), colon cancer (Lara et al 2010), melanoma (O’Connell et al 2010; Castro et al 2022), and breast cancer (Henry et al 2015). In contrast, ROR2 has anti‐oncogenic functions in endometrial (Henry et al 2018), colon (Ma et al 2016), and gastric (Yan et al 2016) cancer as well as in medulloblastoma (Lee et al 2013), hepatocellular carcinoma (Nishita et al 2006) and melanoma (Castro et al 2021). The effect of ROR2 in cancer is mediated by the regulation of cell proliferation, cell migration and invasion, and in vivo tumor growth, which are modulated either positively or negatively depending on the tumor type.…”
Section: Introductionmentioning
confidence: 99%
“…ROR2 played as a tumor promoter in non‐small cervical cancer (Sun et al 2015), renal cell carcinoma (Wright et al 2009; Yang et al 2017), colon cancer (Lara et al 2010), melanoma (O’Connell et al 2010; Castro et al 2022), and breast cancer (Henry et al 2015). In contrast, ROR2 has anti‐oncogenic functions in endometrial (Henry et al 2018), colon (Ma et al 2016), and gastric (Yan et al 2016) cancer as well as in medulloblastoma (Lee et al 2013), hepatocellular carcinoma (Nishita et al 2006) and melanoma (Castro et al 2021). The effect of ROR2 in cancer is mediated by the regulation of cell proliferation, cell migration and invasion, and in vivo tumor growth, which are modulated either positively or negatively depending on the tumor type.…”
Section: Introductionmentioning
confidence: 99%
“…Activated ERK1/2 can regulate the relative proteins involved in proliferation and apoptosis, such as Bad, Bcl-2, and C-myc, thereby contributing to melanoma growth [ 25 , 26 ]. In addition, the Akt pathway is another significant pathway in melanomagenesis, promoting melanoma cell proliferation, metastasis and drug resistance, inhibiting apoptosis, and stimulating DNA mutation [ 27 , 28 ] and is associated with poor survival [ 29 ]. Therefore, our results provide the first evidence of a causal relationship between HSDL2 expression and the ERK and Akt signalling pathways in human melanoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike what was described in other cancers, the dual role of ROR2 in melanoma is associated with the regulation of different biological processes. We have shown that ROR2 impairs cell cycle progression and consequently inhibits the proliferation of melanoma [ 3 ]. However, ROR2 also promotes migration, epithelial to mesenchymal transition (EMT), and chemoresistance in the same cell lines [ 4 , 5 ].…”
Section: Main Textmentioning
confidence: 99%
“…In contrast, the biochemical function of ROR2, a tyrosine kinase receptor (TKR), is completely different, a fact that can be viewed as an impediment to regulating "phenotype switching". However, similar to other TKR important in melanoma such as AXL and EGFR [13], ROR2 does alter the expression of numerous proteins in melanoma [3][4][5] and other cancers [14]. Although the precise mechanism has not been completely elucidated, the signal triggered by aberrant ROR2 expression can be transduced by different signaling pathways and modulate transcription factor activity (i.e.…”
Section: Main Textmentioning
confidence: 99%